Decoding behavioural responses of green hotel guests A deeper insight into the application of the theory of planned behaviour - Olya, Hossein G. T.; Bagheri, Pourya; Tumer, Mustafa (Emerald Group Publishing Ltd, 2019)
Purpose - This study aims to present a unique perspective on the application of the theory of planned behaviour (TPB) in the context of the green lodging industry via configurational modelling of three TPB dimensions in formulating hotel visitors' behavioural responses. Attitude towards behaviour, subjective norms and perceived behavioural control are the three indicators of TPB used to predict guests' continued intention to use and recommend green hotels on Cyprus, a Mediterranean island with a fragile ecological system. Design/methodology/approach - A questionnaire-based survey is used to evaluate the study's objectives. A total of 320 guests of green hotels were approached between June and July 2017 and invited to participate. Among them, 260 valid cases were obtained and used for data analysis. The structural model was tested using structural equation modelling (SEM), the configurational model was assessed using the fuzzy-set qualitative comparative analysis (fsQCA) and the necessary predictor was evaluated using the necessary condition analysis (NCA). Findings - The SEM results revealed that attitudes regarding behaviour increased the continued intention to visit and recommend green hotels. Similarly, subjective norms enhanced the guests' desired behavioural responses. Perceived behavioural control boosted their continued intention to visit, but this was insufficient for predicting green hotel guests' intention to recommend. The fsQCA results indicated that two causal models explained the conditions of both high and low levels of behavioural responses. The NCA results showed that attitude towards behaviour was the only necessary condition of the two expected behavioural responses. Originality/value - Several previous studies have tried to modify, decompose or merge the TPB to provide theoretical support for proposed conceptual models indicating visitors' behaviours. Beyond such attempts, pragmatic analytical approaches (e.g. set-theoretic method) should be applied to present a comprehensive perspective on the association of TPB indicators in decoding the complexity of customers' behaviours. To the best of the authors' knowledge, this study is among the first in hospitality research to use three TPB indicators and three analytical approaches to extend the knowledge of guests' behaviours related to green hotels.
Keywords: Green hotel; Theory of planned behaviour; Ethical consumption; Configurational model; Moral customer; Necessary condition